PENGARUH FAKTOR PSIKOLOGIS TERHADAP HASIL BELAJAR SISWA: STUDI KESEHATAN MENTAL DAN COPING STRESS DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 11 PEKANBARU - Alya Mardatillah B; Zaitun Zaitun; Masyhuri Masyhuri (TABYIN: JURNAL PENDIDIKAN ISLAM, 2025)
This study attempts to examine the impact of students' mental health and stress coping mechanisms on their academic performance in Islamic Religious Education at State Senior High School 11 Pekanbaru. This study utilizes a quantitative methodology including a correlational design. The demographic comprises all Muslim students at State Senior High School 11 Pekanbaru, amounting to 634 students. The research sample included 215 Muslim students from the twelfth grade. Data gathering methodologies encompass surveys and documentation. Data analysis methodologies encompass basic linear regression and multivariate linear regression. The study's findings indicate the following: Mental health significantly affects students' learning results in Islamic Religious Education at State Senior High School 11 Pekanbaru, evidenced by an R-Square (r²) value of 0.151. The impact of coping with stress on students' learning results in Islamic Religious Education at State Senior High School 11 Pekanbaru is substantial, evidenced by an R-Square (r²) value of 0.185. Third, there exists a notable concurrent impact of mental health and coping stress on students' academic performance in Islamic Religious Education at State Senior High School 11 Pekanbaru, evidenced by an R-Square (r²) value of 0.239.